RPE Adenocarcinoma as the Presenting Sign of Bronchogenic Carcinoma: Diagnostic Dilemma in the Management of a Case - Namrata Adulkar; Santhi Radhakrishnan; N. Vidhya; Usha Kim (Case Reports in Ophthalmological Medicine)
Neoplasms of retinal pigment epithelium are rare and must be differentiated from choroidal melanoma. The possibility of a metastatic disease with possible primary sites as lung, breast, or kidney should be ruled out. Herein we report a case of adenocarcinoma arising from the RPE with a lung lesion suspicious of bronchogenic carcinoma. In this paper, ocular symptoms were the first sign of a systemic malignancy.